2008
DOI: 10.1037/a0014195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxytocin and prosocial behavior on brain responses to direct and vicariously experienced pain.

Abstract: In this study, we tested the validity of 2 popular assumptions about empathy: (a) empathy can be enhanced by oxytocin, a neuropeptide known to be crucial in affiliative behavior, and (b) individual differences in prosocial behavior are positively associated with empathic brain responses. To do so, we measured brain activity in a double-blind placebo-controlled study of 20 male participants either receiving painful stimulation to their own hand (self condition) or observing their female partner receiving painfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
152
3
6

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(173 citation statements)
references
References 73 publications
11
152
3
6
Order By: Relevance
“…In this context we note that the insula responds both to the actual feeling of pain and also to pain being experienced by someone else (42)(43)(44). Although a previous study failed to find any effect of OXT on pain empathy in a paradigm where subjects watched their partner receiving a painful procedure (42), this was arguably a much more salient stimulus than for the subjects in our current study viewing aversive pictures. Indeed, two studies reporting OXT effects on empathy using the "reading the mind in the eyes" (32) or a test of empathic accuracy (45) found that these effects were influenced by task difficulty or initial empathy level.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…In this context we note that the insula responds both to the actual feeling of pain and also to pain being experienced by someone else (42)(43)(44). Although a previous study failed to find any effect of OXT on pain empathy in a paradigm where subjects watched their partner receiving a painful procedure (42), this was arguably a much more salient stimulus than for the subjects in our current study viewing aversive pictures. Indeed, two studies reporting OXT effects on empathy using the "reading the mind in the eyes" (32) or a test of empathic accuracy (45) found that these effects were influenced by task difficulty or initial empathy level.…”
Section: Discussioncontrasting
confidence: 45%
“…We have shown previously that OXT elevates emotional empathy responses toward pictures of individuals expressing either strong negative or positive emotions (12). In our present study increased activation of the anterior insula for subsequently remembered negative items following OXT treatment may also reflect enhanced empathy and compassion (42), although in this case, empathy and compassion for the pain being suffered by individuals depicted in most of the stimuli. In this context we note that the insula responds both to the actual feeling of pain and also to pain being experienced by someone else (42)(43)(44).…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…By contrast, deliberate 15 control of empathy for physical pain (PP obj > PP emp ) did not result in decreased activity in 16 any brain regions, and resulted in increased activity in bilateral anterior insula, dorsal and 17 anterior ACC, right OFC, and right TPJ ( Figure 6B; Table 5 In the PPI analysis (also corrected for multiple comparisons using Monte Carlo 23 based permutations, p<0.05) the amygdala was more strongly associated during EP 24 to first-hand physical pain, but has no effect on amygdala activity when another is 21 experiencing that same pain (Singer et al, 2008). These results are consistent with the 22 data from the present study, which show that the amygdala is insensitive to the deliberate 23 control of empathy for others experiencing physically painful events.…”
Section: Acc and Left Orbitofrontal Cortex (Ofc) (Corrected For Multmentioning
confidence: 98%
“…Second, 17 exogenous oxytocin administration in neurotypical adults enhances both amygdala 18 responses and reported empathy for others' suffering (Hurlemann et al, 2010). However, 19 oxytocin administration has no effect on amygdala activity or reported unpleasantness 20 while watching another person in the same room receive physically painful shocks 21 (Singer et al, 2008). Thus, to understand the role of the amygdala in empathy, and 22 empathic regulation, it may be necessary to explicitly distinguish between empathic 23 responses toward others' pain versus their suffering.…”
Section: Amygdala and Empathy 1mentioning
confidence: 99%